Can tamsulosin facilitate expulsion of ureteral stones? A meta‐analysis of randomized controlled trials. (20th December 2012) - Fan, Bo; Yang, Deyong; Wang, Jianbo; Che, Xiangyu; Li, Xiancheng; Wang, Lina; Chen, Feng; Wang, Tiezheng; Song, Xishuang
Abstract : Objectives: To determine the efficacy and safety of the adrenergic alpha‐antagonist tamsulosin in facilitating ureteral stones expulsion. Methods: A literature search was carried out using the PubMed database, Medline via Ovid, Embase and the Cochrane Library database to identify randomized controlled trials evaluating the efficiency of tamsulosin in the treatment of ureteral stones. Meta‐analysis and forest plots were carried out by use of Review Manager version 5.1 software (Cochrane Collaboration). Results: Compared with the control group, the tamsulosin group had an increase in expulsion rate of 51% and a decrease in expulsion time of 2.63 days. Furthermore, tamsulosin was found to reduce the risk of ureteral colic during treatment by 40% and also the risk of requirement of auxiliary procedures during follow up by 60%. In terms of safety, the tamsulosin group had a 117% increase in the incidence of side‐effects compared with the control group, especially for incidence of dizziness. Conclusion: Tamsulosin facilitates the expulsion of ureteral calculi by providing a higher expulsion rate, a shorter expulsion time, a lower incidence of ureteral colic during treatment and a lower requirement of auxiliary procedures. However, the incidence of dizziness occurring during tamsulosin treatment is significantly higher in this setting.